Effect of commercially-available yogurts on streptococcus mutans - Barrientos, Aviane Chakri B.; Corpus, Nuelle Bianca V.; Dimanlig, Anna Maria C.; Rebueno-Santos, Jessica K. Rebueno
Introduction. Probiotics, such as Lactobacillus bulgaricus and Streptococcus thermophilus used as yogurt starter cultures, have been successfully used to control gastro-intestinal diseases and according to studies (Stamatova et al., 2009; Bonifait et al., 2009), these may exert beneficial effects in the oral cavity by inhibiting cariogenic streptocicci (Bushan et al., 2010) and periodontopathogenic bacteria. Lactic acid bacteria can produce different antimicrobial components (Yesilik et al., 2011) which may also benefit the oral microflora. However, data is still sparse on the probiotic action in the oral cavity. The purpose of the study was to determine the antimicrobial activity of commercially-available yogurts against S. mutans. It also aimed to determine the changes in yogurt's pH in time.
Materials and Methods. The antimicrobial activity of commercially-available yogurts was tested on two separate occasions, on 12 plates using the Agar Disc Diffusion Test where two plates of Brain Heart Infusion Agar and Blood Agar with five discs each were used for a given group, and also on 12 plates using Agar Well Diffusion Test where two plates of BHIA with four wells each were used for a given group. The positive control used was chlorhexidine, while the negative controls used were normal saline solution and distilled water, respectively. The diameters of zone of inhibition were measured and interpreted. The data from the experimental group were compared against those of the control groups.
Results. The results showed that all commercially-available yogurts (p=0.00), as well as the negative control group (p=0.00), used in the study exhibited no zones of inhibition. Only the positive control group (p=o0.00) exhibited zones of inhibition. The zones of inhibition for all samples and groups were tabulated. Using the Kruskal-Wallis test, the data were analyzed and the significant group identified.
Conclusion. Commercially-available yogurts used in this study have no antimicrobial activity against Streptococcus mutans, using Agar Disc Diffusion Test and Agar Well Diffusion Test.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Oral health